A Study on Effect of GTAW Current on the Properties of the AISI304 and AISI316L Stainless Steel Tube Joint Properties - Ruksut, Chanerin; Kanchana, Rapee; Kimapong, Kittipong; Chantasri, Sakchai (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to study an effect of GTAW current on a tube butt joint Properties of AISI304 and AISI316L stainless steel using ER309LSi filler metal. A relation of the welding current and the joint properties was systematically investigated. The welding parameters in this study were studied for tensile strength, macrostructure, and hardness was investigated and analyzed. The summarized results were as follows. The tube joint of AISI304 and AISI316Lwas successfully welded by GTAW and was reached a sound joint when the welding current of 100-160 A was applied. Increasing the welding current resulted in an increase in tensile strength and elongation of the weld joint and hardness of the weld metal. The maximum tensile strength and the elongation of 609 MPa and 58% were found when the welding current of 140 A was applied to weld the butt joint. The fracture location of the tensile strength specimen that showed a sound weld metal was at the weld metal area because of the higher hardness and the reduction of the cross section of the weld metal. While the fracture location of the joint that showed incomplete weld metal was found at the center of the weld metal.